Quadro evolutivo de paleocabeceira de drenagem do rio Chopinzinho - Planalto das Araucárias (superfície 2) - Fachin, Andressa (2013)
This thesis presents the paleovalley head evolution in the Chopinzinho drainage basin inside Araucária Plateau (Planation Surface 2), aiming to understand the landscape evolution in the South Brazil during the Upper Quaternary. The stratigraphic record was characterized using the combined criteria of pedo-, litho-, allo-, and cronostratigraphic, for which chronology was establish by 14C (AMS) and thermoluminescence. As base these criteria was utilized following technical: field survey, laboratory analyses (textural, ten major oxides more zirconium oxide, clay mineralogy, and dating) and office work (cluster statistical analysis and organization of date). It has been done the reconstitution spatial distribution of the paleosol and paleogullies by drilling. The field survey showed stratigraphic section in the cutting rural road. Therein was identified paleosol with Ab horizon (27.36 + 0.14 Kyr BP 44.13 Kyr cal. BP), paleogullies field of colluvium (15 beds), colluvium-alluvial (4 beds) and alluvial (1 bed). The colluvium beds was divided into clogging faces and ramp faces. The paleogullies were generated in Last Glacial Maximum (< 24 Kyr to > 17 Kyr BP.) and in Medium Holocene (< 7 Kyr to > 4 Kyr BP). This last moment were generated two paleogullies generations promoting the larger erosion phenomenon in the paleovalley head. The paleovalley head happens to be clogging in the Upper Holocene (< 4 Kyr BP) and change of the morphology becoming colluvium ramp. The palleovalley head was eroded by spot drainage and becoming one convex mound in the end of period. This moment there was one inversion of the relief.